The Impact of Covid-19 Pandemic on Students' Sedentary Behavior in Indonesia - Syiva Fitria; Dedy Surya (JURNAL SERAMBI ILMU, 2021)
Indonesia is one among many countries applies lockdown or large-scale social restriction in order to suppress transmission rates. The current study examines the impact of COVID-19 pandemic lockdown decision on sedentary behavior among adolescents in Indonesia. An online survey was administered to 255 adolescents on August until October. The online survey consists of questions on demographic information and Adolescence Sedentary Activity Questionnaire (ASAQ). Statistical analysis was performed to compare the difference between total hours spend on performing sedentary behavior before and after the pandemic. A paired sample t-test revealed there was a significant difference in total hours spend on performing sedentary behavior before and after the pandemic (t (254) = -12.8, p.001). Adolescence is performing more sedentary behavior after the pandemic (M=10.43, SD=3.11) compared to the time before the pandemic (M=8.68, SD=3.47). In conclusion, the covid-19 pandemic cause change on sedentary behavior where there were increase of the total hour adolescence spend on performing sedentary behavior, including a significant change in learning behavior.